Strategi lembaga perlindungan anak dalam menangani kasus pelecehan seksual di Kota Mataram - Ananda Kurnia Rika; Bagdawansyah Alqadri; Ega Anzani (Departemen Pendidikan Kewarganegaraan dan Ilmu Hukum Universitas Negeri Padang, 2026)
Child sexual abuse is a serious problem that requires comprehensive and collaborative handling. This study aims to analyze the strategies of the Mataram City Child Protection Agency (LPA) in handling sexual abuse cases and identify supporting and inhibiting factors in its implementation. The study used a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and documentation with LPA administrators, case counselors, and related parties. The results indicate that LPA strategies include legal and psychological assistance for victims, cross-sectoral coordination with the police, UPTD PPA, health workers, and educational institutions, as well as preventive efforts through community outreach and education. Supporting factors include inter-institutional cooperation and the commitment of counselors, while inhibiting factors include limited resources, low public awareness, and victim trauma. This study concludes that LPA plays a strategic role, but requires capacity building and ongoing support for optimal handling.